Procatechuic acid and protocatechuic aldehyde increase survival of Caenorhabditis elegans after fungal infection and inhibit fungal virulence - Yuan, Chunyan; Wang, Yuxing; Zhang, Le; Wang, Dayong (Frontiers in Pharmacology, 2024)
D. Wang) Protocatechuic acid (PCA) and protocatechuic aldehyde (PAL) are important phenolic compounds in plants. We here investigated their possible beneficial effect against fungal infection and the underlying mechanism. The model animal of Caenorhabditis elegans was used as host, and Candida albicans was used as fungal pathogen. The nematodes were first infected with C. albicans, and the PCA and PAL treatment were then performed. Post-treatment with 10-100 μM PCA and PAL suppressed toxicity of C. albicans infection in reducing lifespan. Accompanied with this beneficial effect, treatment with 10-100 μM PCA and PAL inhibited C. albicans accumulation in intestinal lumen. In addition, treatment with 10-100 μM PCA and PAL suppressed the increase in expressions of antimicrobial genes caused by C. albicans infection. The beneficial effect of PCA and PAL against C. albicans infection depended on p38 MAPK and insulin signals. Moreover, although treatment with 10-100 μM PCA and PAL could not exhibit noticeable antifungal activity, PCA and PAL treatment obviously suppressed biofilm formation, inhibited hyphal growth, and reduced expressions of virulence genes (ALS3, CaVps34, Vma7, Vac1, and/or HWP1) related to biofilm formation and hyphal growth in C. albicans. Therefore, our data demonstrated the potential of PCA and PAL post-treatment against fungal infection and fungal virulence.